2016
DOI: 10.21037/tau.2016.02.05
|View full text |Cite
|
Sign up to set email alerts
|

Can lifestyle modification affect men’s erectile function?

Abstract: Erectile dysfunction (ED) is a common condition affecting millions of men worldwide. The pathophysiology and epidemiologic links between ED and risk factors for cardiovascular disease (CVD) are well-established. Lifestyle modifications such as smoking cessation, weight reduction, dietary modification, physical activity, and psychological stress reduction have been increasingly recognized as foundational to the prevention and treatment of ED. The aim of this review is to outline behavioral choices which may inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 60 publications
1
21
0
2
Order By: Relevance
“…A recent meta-analysis did not find any association between statin use and new onset ED ( 95 ). Several studies have shown that weight loss, increase of physical activity, smoking and alcohol cessation, as well as stress reduction, are important prevention strategies to tackle sexual dysfunction and other health implications ( 96 ). So far, few studies examined the effect of physical fitness in men with ED on health outcomes.…”
Section: Reproduction/sex Hormones-related High-risk Groups and Intermentioning
confidence: 99%
“…A recent meta-analysis did not find any association between statin use and new onset ED ( 95 ). Several studies have shown that weight loss, increase of physical activity, smoking and alcohol cessation, as well as stress reduction, are important prevention strategies to tackle sexual dysfunction and other health implications ( 96 ). So far, few studies examined the effect of physical fitness in men with ED on health outcomes.…”
Section: Reproduction/sex Hormones-related High-risk Groups and Intermentioning
confidence: 99%
“…These findings clearly imply that exercise is deeply associated with the serum testosterone level and thus with ED, a classic symptom of TD [ 14 ]. However, it is unclear which type of exercise would be better for improving symptoms and the endocrinologic status of patients with TD.…”
Section: Discussionmentioning
confidence: 99%
“…15,41 Clinical data show that ED is an increasingly common condition predicted to affect more than 300 million men worldwide by 2025. 42,43 The increasing rates may reflect the increasing stress in society and could contribute to declining the birth rate that is becoming a serious social problem in certain societies. 43 It has long been established that ED is a multi-factorial dysfunction, but most treatments, including sildenafil citrate, have targeted penile vasculopathy.…”
Section: Discussionmentioning
confidence: 99%
“…42,43 The increasing rates may reflect the increasing stress in society and could contribute to declining the birth rate that is becoming a serious social problem in certain societies. 43 It has long been established that ED is a multi-factorial dysfunction, but most treatments, including sildenafil citrate, have targeted penile vasculopathy. 44 Current treatments can have unwanted side effects and, importantly, fail to address the underlying neural control problem.…”
Section: Discussionmentioning
confidence: 99%